the Relationship between A Skinfold Thicknesses with Level of High Sensitivity C-Reactive Protein in Elderly Woman - Aini, Chanifatunnisa Nurul; Ardiaria, Martha (Sports Medicine Curiosity Journal, 2022)
Aging causes changes in body composition such as a decrease in muscle mass and an increase in adiposity associated with inflammation. High sensitivity C-reactive protein is the marker of inflammation. This study aimed to analyze the relationship between Skinfold Thicknesses with the Level of High Sensitivity C-Reactive Protein in Elderly women. This observational study used a cross-sectional design. Subjects were determined using consecutive sampling and adjusted for inclusion criteria with minimal sample were 53 subjects. Data collected were skinfold thicknesses measured with skinfold caliper and serum HsCRP analyzed by Enzyme-linked Immunosorbent Assay (ELISA), physical activity level measured by International Physical Activity Questionnaire, and dietary intake measured by food recall 3 x 24 hours. Data analysis using Ranks Spearman correlation test. The median value thickness of the biceps is 17.94 ± 10.60 mm, the thickness of the triceps skinfold thickness is 23.40 ± 8.06 mm, the subscapular skinfold thickness is 14.95 ± 7.48 mm, the suprailiac skinfold thickness is 17.00 ± 8.85 mm while the median HsCRP serum 2.09 ± 2.11 mg/L is classified as moderate. There was a relationship between suprailiac skinfold thickness (r = 0.45 p = 0.001) and subscapular (r =0.40 p =0.003). However, there was no relationship between biceps skinfold thickness (r =0.29 p =0.34) and triceps (r=0.75 p =0.47) with HsCRP levels. There was a significant relationship between suprailiac and subscapular skinfold thickness. However, there was no significant relationship between biceps and triceps skinfold thickness.